Trypanosoma congolense: High erythropoietic potential in infected yearling cattle during the acute phase of the anemia - Andrianarivo, A.G.; Muiya, P.; Logan-Henfrey, L.L. (Elsevier, 1996)
N'Dama (Bos taurus) cattle are known to tolerate trypanosome infections, developing less severe anemia and lower parasitemia, compared to Boran (Bos indicus) cattle. Young calves were also reported to be more resistant to trypanosomiasis than adult cattle. To expore the basis for this resistance, the erythropoietic response was evaluated in four naive yearling N'Dama calves and four age-matched Boran calves which developed anemia over a 140-day primary infection with Trypanosoma congolense clone IL 13E3. Similar levels of parasites were detected in the two breeds until 42 days postinfection (dpi). During the same period, a rapid and greater colony-forming units-erythroid response in the bone marrow of yearling Boran calves, compared with N'Dama calves, may explain the unusual absence of breed differences in mean packed cell volumes (PCV). However, this early erythropoietic response was transient and did not result in any rise in PCV in the Boran calves. Moreover, dispite the persistent severe anemia, the erythroid response subsided from 70 dpi onward. In contrast, in the N'Dama calves, following the erythroid response, the mean PCV was gradually compensated from 56 dpi onward and reached 30 percent by 126 dpi. This period of PCV recovery coincided with low and intermittent parasitemia and a return of the erythroid progenitor levels to near preinfection values. Elevated levels of erythroid progeniotrs in the N'Dama calves, occurring 1 week after trypanocidal treatment, returned the PCV to preinfection values. These results suggest that the age of the Bos indicus cattle has important impact on the early bone marrow response in primary T. congolense infection and confirmed previous suggestions of a high erythropoietic potential in trypanosome-infection and confirmed previous suggestions of a high erythropoietic potential in trypanosome-infected young calves.